Insights into Biohydrogen Production Through Dark Fermentation of Food Waste: Substrate Properties, Inocula, and Pretreatment Strategies - Djangbadjoa Gbiete; Satyanarayana Narra; Damgou Mani Kongnine; Mona-Maria Narra; Michael Nelles (Energies)
The growing population and economic expansion have led to increased energy demand while presenting complex waste generation and management challenges, particularly in light of climate change. Green hydrogen, which is considered a major clean energy carrier, can also be generated from food waste through a process known as dark fermentation. The production of dark fermentative hydrogen from food waste and biomass residues, in general, is influenced by the type of feedstock, source of inoculum, and their pretreatment and handling strategies. Food waste is a suitable substrate for dark fermentation and has a variable and complex composition, which is a major factor limiting the hydrogen yield. This review critically assesses food waste sources, focusing on their physical and chemical composition, pretreatment methods, and strategies for optimizing dark fermentative hydrogen production. This paper also highlights and critically discusses various inoculum sources and innovations regarding the pretreatment and enrichment applications of inocula for dark fermentative hydrogen production. Based on the literature analysis, advanced research is required to develop more sustainable and specific pretreatment strategies that consider the properties of food waste and the source of the inoculum. This approach will aid in preventing inhibition and inefficiency during the dark fermentation process.